Diagnosis of glucocorticoid-remediable aldosteronism in hypertensive children - Kamrath, Clemens; Maser-Gluth, Christiane; Haag, Christine; Schulze, Egbert (Hormone research in paediatrics, 2011)
Objective: Glucocorticoid-remediable aldosteronism (GRA) is caused by the presence of a chimeric gene originating from an unequal cross-over between the CYP11B1 and CYP11B2 genes. Aldosterone suppression by dexamethasone and high 18-hydroxycortisol (18-OHF) levels have been used to differentiate GRA from the other forms of primary aldosteronism. Methods: A dexamethasone suppression test including serum 18-OHF determination and the measurement of urinary excretion of aldosterone, its metabolites and 18-OHF were performed in 3 children of a family with primary aldosteronism. Polymerase chain reactions were performed to identify the chimeric gene. Results: The chimeric gene was identified in 2 children, their mother and grandmother. The affected children had an aldosterone-to-plasma renin activity ratio >30, elevated serum 18-OHF concentration and increased urinary excretion of aldosterone, its metabolites, and 18-OHF. Post-dexamethasone concentrations of serum aldosterone and 18-OHF concentrations were suppressed. Conclusion: Although very rare, the possible diagnosis of GRA should be considered in all children or young adults with low-renin hypertension. Since genetic testing is more specific than biochemical testing, a definitive diagnosis can only be obtained by identification of the CYP11B1/CYP11B2 chimeric gene.